Testen sprachlicher Kompetenzen von Lehramtsstudierenden - Ergebnisse im Lichte sprachlichen Wandels - Grütz, Doris (My University, 2011)
At the Zurich University of Teacher Education, all students are examined in their German language competence make sure that they have sufficient language knowledge, which is a prerequisite for study-ing to be a primary or secondary school teacher. The exam is based on a model of language compe-tence which refers to language awareness. This concept is based on a two-dimensional construct of language awareness which includes, on the one hand, the formal competence of the correct usage of grammar, semantics of words and orthography, and on the other hand, the testing of the usage of lan-guage by written composition. The language data which result from the exams show forms of language transition, which means the linguistic changes taking place in the community of German language speakers. Examples will demonstrate in which areas norm-oriented insecurity prevails and which effect this has on task conception.
Keywords: Sprachwandel; Deutschkompetenz; Sprachbewusstheit; Testen schriftsprachlicher Kompetenzen